(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to try to identify “the effect of the interactive teaching strategy on the expressive performance of female second-year intermediate students.” , To achieve the goal of the research, the researcher formulated the null hypothesis, which stated: “There are no statistically significant differences at the level of significance (0.05) between the average grades of the female students of the experimental group who are studying the subject of expression according to the interactive teaching strategy and the average grades of the female students of the control group who are studying the same subject according to the interactive teaching strategy.” "According to the usual method." The researcher followed the experimental approach and relied on an experimental design with two groups, experimental and control. The research population was represented by female students in the second intermediate grade in the General Directorate of Education in Baghdad/Al-Rusafa II. The researcher randomly selected “Al-Irada Girls” middle school as a sample for her research. The number of students in the experimental group was (30) male and female students. The control group consisted of (31) female students, and the researcher statistically rewarded the two research groups (experimental and control) using the variables “the chronological age of the female students calculated in months, the parents’ achievement, and the expressive performance test scores.” The researcher prepared a questionnaire that included (12) expressive topics, which she presented to a group of arbitrators, to choose (7) topics from them. The researcher used a unified tool to measure the expressive performance of the female students of the two research groups. She prepared a series of achievement tests for the purposes of her research to be applied to the two research groups (experimental and control). At the end of each topic, based on the criteria for correcting Al-Rubaie (1997) . Using the t-test for two independent samples, the researcher found that there were statistically significant differences at the significance level (0.05) in favor of the female students of the experimental group who were studying the subject of expression according to the interactive teaching strategy. The researcher recommended adopting an interactive teaching strategy in teaching expression for the second intermediate grade, and suggests conducting a number of similar studies for different educational levels and for both genders.